Modeling, simulation and experimental validation of the properties of macro-scale piezoelectric cantilevers for deduction of mass sensitivity of micro-cantilevers - Ahmed, M.G.A. (Research India Publications, 2016)
This article describes the modeling, simulation and experimental verification of the properties of five different macro-scale piezoelectric (PZT) cantilevers for the prediction and deduction of properties of their micro-scale counterparts in relation to their mass sensitivity. In order to investigate the relationship between resonant frequency, quality factor and mass sensitivity, piezoelectric cantilevers of different lengths from 40 mm to 10 mm are utilized keeping the other parameters constant. On the basis of the test definition and the feedback received from a reference accelerometer is mounted on shaker table, the control signal is generated by the controller unit, and the signal is amplified using an IMV MA1 type amplifier that can produce a maximum output. Then the amplified signal is fed to the shaker unit. The output from the piezoelectric is recorded and analyzed using a DEWE-3023-dsa-x type dynamic signal analyzer. Different masses are attached to the free end of the cantilevers and the change in resonance frequency measured. The main advantages of cantilevers as sensing mechanisms are their high sensitivity, low cost, high response, and low power consumption. Through this study we discover that the sensitivity is a strong function of attached mass, highest sensitivity achieved at law attached mass and stumpy PZT cantilever. Â© 2016, Research India Publications.